Nephrological Aspects of Balneotherapy with Uvinskaya Mineral Water in Patients with Type 2 Diаbetes - Aleksei E. Shklyaev; Daniil D. Kazarin; Yurii V. Gorbunov; Petr I. Chetverikov; Mikhail V. Kuzyaev (Кубанский научный медицинский вестник, 2019)
Aim. The present article studies the effect of balneotherapy with Uvinskaya mineral water on the microbial spectrum of urine in patients with type 2 diabetes.Materials and methods. The study was carried out at the Endocrinology Department of the First Republican Clinical Hospital (Izhevsk). A total of 56 patients with type 2 diabetes participated in the study, which involved collecting medical history and complaint data of patients along with performing general and system-based examination, urinalysis, urine culture prior to and following the course of therapy, as well as kidney ultrasound aimed at excluding the presence of calculi. Urine cultures (morning sample) were plated onto 5% blood agar, as well as Endo’s medium for detecting bacteria from the Enterobacteriaceae family using the Gould method. Urine cultures were incubated for 24, 72 and 144 hours at a temperature of 37 °C. The significance of differences was determined using the t-test for independent and paired samples.Results. Changes in urinalysis were observed in all examined patients, which included changes characteristic of urinary tract infections: a large number of bacteria per field of view; a large amount of mucus; the presence of leukocytes in urine; alkaline pH shift; as well as disorders typical of diabetes mellitus (glycosuria, proteinuria). E. coli predominated in urine cultures. Following a 30-day therapy with Uvinskaya mineral water, the number of bacteria and leukocytes, as well as the amount of mucus, detected in the urine reduced significantly, which indicates urinary tract sanation. Positive dynamics among patients who underwent balneotherapy treatment is confirmed by the Student’s t-test (p < 0.05). In addition, no urinary sanation was observed in the group of patients who did not receive balneotherapy.Conclusion. Drawing on the study results, the authors recommend using Uvinskaya natural mineral water in the combined treatment of patients with type 2 diabetes for urinary tract rehabilitation.